GIS modeling in raster - Demers, Michael N. (John Wiley & Sons, 2001)
The primary focus of this text is on the process of cartographic modeling and GIS modeling. The text goes beyond cartographic modeling to incorporate supplementary or complementary technologies and logics to show that spatio-temporal modeling is not limited to cartographic modeling, nor to Map Algebra. DeMers consistent, friendly and engaging style has been highly praised by reviewers of this title as well as users of his market leading Fundamentals of Geographic Information Systems